The Networks of Genes Encoding Palmitoylated Proteins in Axonal and Synaptic Compartments Are Affected in PPT1 Overexpressing Neuronal-Like Cells - Pezzini, Francesco; Bianchi, Marzia; Benfatto, Salvatore; Griggio, Francesca; Doccini, Stefano; Carrozzo, Rosalba; Dapkunas, Arvydas; Delledonne, Massimo; Santorelli, Filippo M.; Lalowski, Maciej M.; Simonati, Alessandro (Frontiers in Molecular Neuroscience, 2017)
CLN1 disease (OMIM #256730) is an early childhood ceroid-lipofuscinosis associated with mutated CLN1, whose product (PPT1) is a lysosomal enzyme involved in the removal of palmitate residues from S-acylated proteins. In neurons, PPT1 expression is also linked to synaptic compartments. The aim of this study was to unravel molecular signatures connected to CLN1. We utilized SH-SY5Y neuroblastoma cells overexpressing wild type CLN1 (SH-p.wtCLN1) and five selected CLN1 patients’ mutations. The cellular distribution of wtPPT1 was consistent with regular processing of endogenous protein, partially detected inside Lamp2 positive vesicles, while the mutants displayed more diffuse cytoplasmic pattern. Transcriptomic profiling revealed 802 differentially expressed genes (DEGs) in SH-p.wtCLN1 (as compared to empty-vector transfected cells), whereas the number of DEGs detected in the two mutants (p.L222P and p.M57Nfs*45) was significantly lower. Bioinformatic scrutiny linked DEGs with neurite formation and neuronal transmission. Specifically, neuritogenesis and proliferation of neuronal processes were predicted to be hampered in the wtCLN1 overexpressing cell line, and these findings were corroborated by morphological investigations. Palmitoylation survey identified 113 palmitoylated protein-encoding genes in SH-p.wtCLN1, including 25 ones simultaneously assigned to axonal growth and synaptic compartments. A remarkable decrease in the expression of palmitoylated proteins, functionally related to axonal elongation (GAP43, CRMP1 and NEFM) and of the synaptic marker SNAP25, specifically in SH-p.wtCLN1 cells was confirmed by immunoblotting. Subsequent, bioinformatic network survey of DEGs assigned to the synaptic annotations linked 81 DEGs, including 23 ones encoding for palmitoylated proteins. Results obtained in this experimental setting outlined two affected functional modules (connected to the axonal and synaptic compartments), which can be associated with an altered gene dosage of wtCLN1. Moreover, these modules were interrelated with the pathological effects associated with loss of PPT1 function, similarly as observed in the Ppt1 knockout mice and patients with CLN1 disease.